هجرة العمال السوافة إلى البلاد التونسية خلال فترة الحماية الفرنسية (1881 – 1956م) - بريك الإمام; بورغدة رمضان (University of Eloued جامعة الوادي, 2024)
يهدف هذا المقال العلمي إلى دراسة ظاهرة هجرة العمال السوافة وتطورها باتجاه البلاد التونسية خلال فترة الحماية الفرنسية 1881 – 1956م؛ دراسة تاريخية إحصائية، نسعى من خلالها إلى إبراز الدور الذي لعبه العمال السوافة في الحياة الاقتصادية التونسية. لقد أجمعت جميع مصادرنا على الوزن الاقتصادي للعمال السوافة من خلال حضورهم المميز وتفوقهم العددي عبر احصائيات دقيقة، والذي أكّد على تنوع المناطق الطاردة والمستقطبة للهجرة العمالية، حيث ساهمت منطقة وادي سوف بجميع مكوناتها الجغرافية والقبلية في تطورها، وبفضل ذلك التنوع استطاع البعض من العمال تقلد بعض المسؤوليات النقابية في مختلف التنظيمات النقابية التونسية والفرنسية،وتدرج البعض الآخر فيالمناصب والرتب المهنية خاصة في المؤسسات المنجمية بمدينة قفصة. This scientific article aims to study the phenomenon of Souafa worker migration and its development towards Tunisia during the French protectorate period 1881-1956. A historical and statistical study, through which we seek to highlight the role played by Souafa workers in Tunisian economic life. All our sources have unanimously agreed on the economic weight of the Souafa workers through their distinctive presence and numerical superiority through accurate statistics, which confirmed the diversity of the regions that are expelling and attracting labor migration, as the Oued Souf region, with all its geographical and tribal components, contributed to its development, and thanks to that diversity, some workers were able to imitate others. Trade union responsibilities in various Tunisian and French trade union organizations, and others were promoted to professional positions and ranks, especially in mining institutions in the city of Gafsa.
دراسة تاريخية إحصائية
Keywords: هجرة العمال السوافة; البلاد التونسية; تطور تعداد العمال; التنظيمات النقابية; المؤسسات الاقتصادية; Migration of Souafa workers; Tunisia country; Development of the number of workers; Union organizations; Economic institutions